2000
DOI: 10.1136/jech.54.12.885
|View full text |Cite
|
Sign up to set email alerts
|

A minimum income for healthy living

Abstract: Background-Half a century of research has provided consensual evidence of major personal requisites of adult health in nutrition, physical activity and psychosocial relations. Their minimal money costs, together with those of a home and other basic necessities, indicate disposable income that is now essential for health. Interpretation-Accumulating science means that absolute standards of living, "poverty", minimal oYcial incomes and the like, can now be assessed by objective measurement of the personal capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 23 publications
3
76
1
2
Order By: Relevance
“…15 It is also consistent with research identifying a 'minimum income for healthy living' that provides decent food, shelter and clothing plus opportunities for activities that foster social integration (Morris, Donkin, Wonderling, Wilkinson, & Dowler, 2000). Last but by no means least, the goal of increasing the PNA is consistent with the recognition that poverty restricts disabled people's rights to social and political participation (Beresford, 1996).…”
Section: Resultssupporting
confidence: 61%
“…15 It is also consistent with research identifying a 'minimum income for healthy living' that provides decent food, shelter and clothing plus opportunities for activities that foster social integration (Morris, Donkin, Wonderling, Wilkinson, & Dowler, 2000). Last but by no means least, the goal of increasing the PNA is consistent with the recognition that poverty restricts disabled people's rights to social and political participation (Beresford, 1996).…”
Section: Resultssupporting
confidence: 61%
“…However, these studies had a global, rather than European, focus [35]. It appears that in the European countries considered here, more unequal distribution of income leads to a larger proportion of individuals with incomes less than the minimum required for healthy living [42,43], or below the poverty line. Thus, despite the overall wealth and level of economic development within a nation, income inequality increases the numbers of individuals within a country that have low vaccine coverage, engage in high-risk health behaviour, and have limited access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The more theoretical approach of budget standards research, which cost diets appropriate for health for different household types, has demonstrated that, on average, UK families living on low incomes with dependent children (83) , young single men paid at or below the minimum wage (84) and older individuals living on state old-age pensions (85) are likely to have insufficient money to meet basic needs for healthy living, including food. In that they do not, on the whole, go hungry is testament to immense skill in budgeting and managing limited resources, acceptance of monotonous diets and the probability of having to rely on very cheap food that is unlikely to contribute to a healthy dietary intake.…”
Section: Evidence Of Causal Understanding: Inputs and Choicementioning
confidence: 99%